2021
DOI: 10.1038/s42255-021-00395-7
|View full text |Cite
|
Sign up to set email alerts
|

The liver-clock coordinates rhythmicity of peripheral tissues in response to feeding

Abstract: The mammalian circadian system consists of a central clock in the brain that synchronizes clocks in peripheral tissues. While the hierarchy between the central and peripheral clocks is established, little is known regarding the specificity and functional organization of peripheral clocks. Here, we employ altered feeding paradigms in conjunction with liver-clock mutant mice to map disparities and interactions between peripheral rhythms. We find that peripheral clocks largely differ in their responses to feeding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
83
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 91 publications
(89 citation statements)
references
References 72 publications
6
83
0
Order By: Relevance
“…examined clocks in liver, adipose tissue, lung, quadriceps, kidney, and heart and profiled transcriptomes in liver, adipose tissue, and lung in male mice. The findings are consistent with ours, that is, peripheral tissues exhibit distinct patterns of phase entrainment of diurnal transcriptomes to inverted feeding ( Xin et al., 2021 ; Manella et al., 2021 ). Thus, a comparison of AL vs DRF provides strength to our study.…”
Section: Limitationssupporting
confidence: 92%
See 3 more Smart Citations
“…examined clocks in liver, adipose tissue, lung, quadriceps, kidney, and heart and profiled transcriptomes in liver, adipose tissue, and lung in male mice. The findings are consistent with ours, that is, peripheral tissues exhibit distinct patterns of phase entrainment of diurnal transcriptomes to inverted feeding ( Xin et al., 2021 ; Manella et al., 2021 ). Thus, a comparison of AL vs DRF provides strength to our study.…”
Section: Limitationssupporting
confidence: 92%
“…Very recently, Manella et al. have used Alb-Cre+ male mice as the wildtype control, and recapitulated our observations in males under a 30-day inverted feeding, or daytime feeding as they called it ( Manella et al., 2021 ). Sexual dimorphism is emerging as a key factor in studying circadian rhythm ( Anderson and FitzGerald, 2020 ; Weger et al., 2019 ).…”
Section: Before You Beginsupporting
confidence: 72%
See 2 more Smart Citations
“…Feeding rhythm is crucial in clock synchronization in the body ( Reinke and Asher, 2019 ), yet different peripheral clocks seem to respond with a broad spectrum of kinetics ( Xin et al, 2021 ). Inverted feeding readily reverses circadian rhythms in liver and adipose tissue ( Manella et al, 2021 ; Xin et al, 2021 ). Recently, a multi-omics study indicated that diurnal rhythms of transcriptomes, metabolomes, and clocks in the heart and kidney are resistant to circadian entrainment by feeding rhythm ( Xin et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%